ANALISIS DAYA TAHAN PADA PEMBALAP SEPEDA KOTA PEKANBARU NOMOR ROAD RACE - Kunti Indrajati; Zainur Zainur; Syahriadi Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The lack of endurance in cyclists in road competition numbers is one of the problems for athletes, because the distance reaching 80-200 KM, the uphill, downhill and horizontal track is very exhausting, so endurance plays a big role for athletes, especially endurance endurance. The aim of this research is to analyze how strong cyclists' endurance is in race events on the road. The population in this research were all cyclists in Pekanbaru, totaling 15 athlete’s. The sampling technique used is total sampling. The data collection technique is obtained from the pre-test and post-test. The instrument in this research used the bleep test as a tool to measure endurance. based on data analysis and discussion using the percentage formula (%), then obtained from 15 research samples, 1 person is classified as good, 5 people are enough and 9 people are good. Thus, it can be concluded that the endurance of the cyclists of the city of Pekanbaru is classified or can be considered as moderate..Key Words: Endurance Analysis, Bike Racing, Road Race